Integrating Marketing, HRM, and Accounting Systems for Customer Value Sustainability - Raden Agoeng Bhimasta; Rio Ageng Surya; Dismas Persada Dewangga Pramudita (LPPM STIE KRAKATAU, 2025)
Collaborative culture is increasingly regarded as a strategic necessity in modern organizations, particularly as the successful creation of customer value requires strong cross-functional integration. This study aims to explore how collaborative culture is constructed, practiced, and interpreted by employees across three core functions: Human Resource Management, Marketing Management, and Accounting Systems to enhance sustainable customer value. Using a qualitative approach based on literature meta-synthesis and thematic analysis of recent international studies, this article presents an integrative framework to provide a comprehensive understanding of cross-functional interaction dynamics. The findings indicate that the effectiveness of collaboration is influenced by the alignment of strategic goals, the clarity of communication mechanisms, and the degree of data transparency facilitated by accounting systems. Moreover, the HR function plays a central role in fostering trust, shaping collaborative work norms, and encouraging more adaptive cross-divisional practices. These findings offer practical implications for organizations seeking to strengthen interdepartmental integration as the foundation for generating superior customer value. The study also emphasizes that collaborative culture does not emerge instantly; rather, it evolves through reflective processes, social learning, behavioral consistency, and leadership commitment in facilitating cross-functional synergy. Thus, effective collaboration requires continuous interaction between organizational structures, information technology, and human capabilities to create value that is responsive to customer needs. Keywords : Accounting Systems, Marketing Management, Human Resource Management, Collaborative Culture